HUKUM JUAL BELI SAYURAN DARI SUPPLIER KEPADA PENJUAL PERSPEKTIF IMAM NAWAWI (STUDI KASUS DI PASAR HARIAN KECAMATAN SIMPANG KIRI KOTA SUBULUSSALAM) - Kiki Delfianti (ISLAMIC BUSSINESS LAW REVIEW, 2019)
Buying and selling vegetables from supplier to sellers at Simpang Kiri district Subulussalam city’s daily market has a wholesale and perkilo order system. In the practice after the contract, there is a problem where the seller in the market gets vegetables from the supplier with a bad condition or does not deserve to resold. While in the beginning of the contract, the supllier has explained that the vegetables in good condition. The vegetables in a bad condition no get compensation from the supplier. There is any element of Uncertainy (gharar) here. In this Thesis, the authar discusses the law of buying and selling vegetables with the perspective of Imam Nawawi on buying and selling gharar. The type of the research is empirical juridical with field methode combined with the library research methods. The approach taken is a sosiological approach and uses a concept approach. Data collection was done by interview and document study. The law of buying and selling the vegetables from the supplier to the seller in the Simpang Kiri district Subulussalam City’s daily market contains the gharar elemen in terms of Imam Nawawi’ opinion, where the gharar is haram.